Electrocardiography Findings in Children with Febrile Convulsion - Noori, Noor Mohammad; Khajeh, Ali; Teimouri, Alireza (Journal of Pediatric Neurology, 2020)
Febrile convulsion (FC) is a seizure associated with body temperature that leads to electrocardiography changes. This article aimed to study electrocardiographic changes in children with FC as compared with healthy children. In this case–control study, 90 children aged 6 to 60 months were matched with equal healthy ones in “Ali Ebne Abi Talib” hospital in Zahedan, Iran. FC was confirmed by a neurologist based on its definition by the International League Against Epilepsy. Electrocardiogram (ECG) was captured by a pediatric cardiologist. Data were analyzed using SPSS 19. Sex distribution in groups was similar (p = 0.232). QT correction (QTc) was normal in 97.8 and 76.7% of controls and FC children, respectively (p < 0.001). QT dispersion (QTd) was normal in all controls when it was prolonged in 0.6% of children (p< 0.316). Calculated QT (QTcd) prolonged in controls and FC of 4.4 and 27.8% of children, respectively (p < 0.001). RR interval (p = 0.001), heart rate (p< 0.001), S in V1 (p = 0.004), R in aVL (p = 0.007), S in V3(p< 0.001), left ventricular mass (LVM) (p< 0.001), QTd (p< 0.001), QTc max (p< 0.001), and QTcd (p< 0.001) were significant. Means of LVM were 46.00 ± 1.86, 47.22 ± 2.24, and 51.45 ± 2.41 for age groups of <12, 12–24, and >24 months, respectively (p < 0.001). We conclude that QTd, QTc, and QTcd were higher in FC compared with those of healthy children. The rate of FC in children with higher level of QTcd increased compared with controls.
Keywords: electrocardiography; febrile convulsion; children